x2-18x+81 = (x-9)(x-9) when factored
6xyz(3x + 2y + z)
9x2 - 18x + 99(x2 - 2x + 1)==========
Because: (9-x)(9-x) = 81-18x+x^2
Divide all terms by 2 and it can then be factored to (2x+1)(5x+2)
18x + 24 6(3x + 4) is factored fully
(6x + t)(3x + t)
x2-18x+81 = (x-9)(x-9) when factored
6xyz(3x + 2y + z)
9x2 - 18x + 99(x2 - 2x + 1)==========
Because: (9-x)(9-x) = 81-18x+x^2
Divide all terms by 2 and it can then be factored to (2x+1)(5x+2)
3x3+15x2+18x = 3x(x2+5x+6) = 3x(x+2)(x+3)
2(4x - 3)(x + 3)
x2 + 18x = x(x + 18) which cannot be simplified further.
6x5(x2 - 6x + 3)
Divide all terms by 3 and so x2+18x+81= (x+9)(x+9) when factored